(untitled) (Research, Society and Development, 2020)
This study aims to report an experience of applying Project Based Learning (PBL) in the discipline of Cellular and Molecular Biology in a Physiotherapy course. It is an applied research, in the form of a experience report, descriptive and exploratory, with a qualitative approach. The theme chosen for the application of PBL was the assembly of a practical class using the Lactophenol Cotton Blue dye. The PBL steps followed: 1st Motivating question; 2nd proposed challenge; 3rd Research and content; 4th Fulfilling the challenge; 5th Reflection and feedback; 6th Answering the initial question; 7th Assessment of learning. As products of the application of PBL, in addition to the practical class protocol assembled and tested, students proposed the formulation of this article. Final considerations show that the application of PBL in the discipline of Cellular and Molecular Biology of the Physiotherapy course was contemplated the objectives, in the sense that it provided learning inserted in the context of the discipline, taking into account that students became agents in the process of producing your knowledge. One of the difficulties in implementing an active method within a disciplinary curriculum, is the acceptance on the part of the students in executing the methodology, since more protagonism is required from them. Ideally, the method used in the discipline’s teaching plan should be indicated, and if the application of PBL is maintained, it should be indicated in the Pedagogical Course Project whenever possible.